Time-Course Changes and Role of Autophagy in Primary Spinal Motor Neurons Subjected to Oxygen-Glucose Deprivation: Insights Into Autophagy Changes in a Cellular Model of Spinal Cord Ischemia - Chen, Shudong; Tian, Ruimin; Luo, Dan; Xiao, Zhifeng; Li, Hui; Lin, Dingkun (Frontiers in Cellular Neuroscience, 2020)
Spinal cord ischemia is a severe clinical complication induced by surgical interventions of aortic diseases, severe trauma or compression to spinal column. As one of the most important functional neurons in spinal cord, spinal motor neurons (SMNs) suffers most during the process since they are vulnerable to ischemic injury due to high demands of energy. Previous researches have tried various animal models or organotypic tissue experiments to mimic the process and get to know the pathogenesis and mechanism. However, little work has been performed on the cellular model of spinal cord ischemia which has been hampered by the inability to obtain sufficient number of pure primary SMNs for in vitro study. By optimizing the isolation and culture of SMNs, our laboratory has developed an improved culture system of primary SMNs which allows cellular models and thus mechanism studies. In the present study, by establishing a in vitro model of spinal cord ischemia, we intended to observe the dynamic time-course changes of SMNs and investigate the role of autophagy in SMNs during the process. It was found that oxygen-glucose deprivation (OGD) resulted in destruction of neural networks and decreased cell viability of primary SMNs, and the severity increases with the prolonging of OGD time. The OGD treatment enhances autophagy, which reached a peak at 5 h. Further investigation demonstrated that inhibition of autophagy exacerbates the injury, evidencing that autophagy plays protective roles during the process.